Mixed-location cerebral hemorrhage/microbleeds: Underlying microangiopathy and recurrence risk - Pasi, Marco (Neurology, 2018)
OBJECTIVE: To assess the predominant type of cerebral small vessel disease (SVD) and recurrence risk in patients who present with a combination of lobar and deep intracerebral hemorrhage (ICH)/microbleed locations (mixed ICH). METHODS: Of 391 consecutive patients with primary ICH enrolled in a prospective registry, 75 (19%) had mixed ICH. Their demographics, clinical/laboratory features, and SVD neuroimaging markers were compared to those of 191 patients with probable cerebral amyloid angiopathy (CAA-ICH) and 125 with hypertensive strictly deep microbleeds and ICH (HTN-ICH). ICH recurrence and case fatality were also analyzed. RESULTS: Patients with mixed ICH showed a higher burden of vascular risk factors reflected by a higher rate of left ventricular hypertrophy, higher creatinine values, and more lacunes and severe basal ganglia (BG) enlarged perivascular spaces (EPVS) than patients with CAA-ICH (all p < 0.05). In multivariable models mixed ICH diagnosis was associated with higher creatinine levels (odds ratio [OR] 2.5, 95% confidence interval [CI] 1.2–5.0, p = 0.010), more lacunes (OR 3.4, 95% CI 1.7–6.8), and more severe BG EPVS (OR 5.8, 95% CI 1.7–19.7) than patients with CAA-ICH. Conversely, when patients with mixed ICH were compared to patients with HTN-ICH, they were independently associated with older age (OR 1.03, 95% CI 1.02–1.1), more lacunes (OR 2.4, 95% CI 1.1–5.3), and higher microbleed count (OR 1.6, 95% CI 1.3–2.0). Among 90-day survivors, adjusted case fatality rates were similar for all 3 categories. Annual risk of ICH recurrence was 5.1% for mixed ICH, higher than for HTN-ICH but lower than for CAA-ICH (1.6% and 10.4%, respectively). CONCLUSIONS: Mixed ICH, commonly seen on MRI obtained during etiologic workup, appears to be driven mostly by vascular risk factors similar to HTN-ICH but demonstrates more severe parenchymal damage and higher ICH recurrence risk.